2013
DOI: 10.1371/journal.pone.0074042
|View full text |Cite
|
Sign up to set email alerts
|

SMAD7 Variant rs4939827 Is Associated with Colorectal Cancer Risk in Croatian Population

Abstract: BackgroundTwenty common genetic variants have been associated with risk of developing colorectal cancer (CRC) in genome wide association studies to date. Since large differences between populations exist, generalisability of findings to any specific population needs to be confirmed.AimThe aim of this study was to perform an association study between risk variants: rs10795668, rs16892766, rs3802842 and rs4939827 and CRC risk in Croatian population.MethodsAn association study was performed on 320 colorectal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…For example, SMAD7 rs4939827 was found to be associated with CRC in two GWASs [ 74 , 75 ]. The association of SMAD7 rs4939827 with CRC was confirmed by other replication studies [ 76 , 77 ]. A summary of other SNPs studied as risk factors for CRC is shown in Table 8 .…”
Section: Genome-wide Association Study and Colorectal Cancersupporting
confidence: 69%
“…For example, SMAD7 rs4939827 was found to be associated with CRC in two GWASs [ 74 , 75 ]. The association of SMAD7 rs4939827 with CRC was confirmed by other replication studies [ 76 , 77 ]. A summary of other SNPs studied as risk factors for CRC is shown in Table 8 .…”
Section: Genome-wide Association Study and Colorectal Cancersupporting
confidence: 69%
“… 22 Another study revealed the association between SNP of rs4939827 and the risk of CRC in the Croatian population. 36 Rs4464148, located in intron 3 of SMAD7 gene, has also been discovered to be correlated with the risk of CRC in European-ancestry populations. 55 Besides that, Rs4464148 variant genotype of SMAD7 has been proved to be associated with an increased cancer incidence.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of these SNPs in the occurrence of CRC may vary between populations, for example, due to allele frequencies or particular genetic and environmental factors that may modify the effect of the variants. Recognizing the effects in different populations may help in discovering disease mechanism …”
Section: Discussionmentioning
confidence: 99%